Development of E-Commerce Information System at Az-Zahra Shop Using Laravel Framework - Nawaf Naofal; Muhammad Rifqi Daffa Ulhaq; Cahyo Prianto (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
Az-zahra Furniture Store is a furniture store which is located at Jalan Raya Pasar Cipunagara, Subang, West Java. In its business process, as an effort to expand the reach of consumers and move towards digitization, a website-based e-commerce system called e-fazastore is designed which is expected to help az-zahra furniture store in running business processes. With this e-commerce system, it will assist in several activities such as selling and managing furniture data, managing customer order data and facilitating transactions between the two parties, namely the seller and their customers, as well as making it easier to find out the available inventory. The system is built using the Laravel framework with an MVC (Model, View, Controller) architectural design system, which is a design method that divides the program structure into three main parts, namely data (Model), system view (View) and how to operate a data flow (Model). controller) in the system